Isa ibn Ali's book on the useful properties of animal parts : edition, translation and study of a fluid tradition - Raggetti, Lucia (Science, technology, and medicine in ancient cultures, 2018)
The?Science of properties? represents a large and fascinating part of Arabic technical literature. The book of Isa Ibn Ali's (9th cent.)?On the useful properties of animal parts? was the first of such compositions in Arabic. His author was a Syriac physician, disciple of Hunayn ibn Ishaq, who worked at the Abbasid court during the 'floruit' of the translation movement. For the composition of his book, as a multilingual scholar, he collected many different antique and late antique sources. The structure of the text itself?a collection of recipes that favoured a fluid transmission?becomes here the key to a new formal analysis that oriented the editorial solutions as well. The?Book on the useful properties of animal parts? is a new tile that the Arabic tradition offers to the larger mosaic representing the transfer of technical knowledge in pre-modern times. This text is an important passage in that process of acquisition and original elaboration of knowledge that characterized the early Abbasid period.